The Principles of Organization of Internal Control of Companies - Panteleiev, V. P. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The question to give a convincing assessment of the Rules of the internal controls and present them in the form of principles of organization of internal control. Since the final decision in the form of an exhaustive list and universal principles of internal control is no scientific research continues these principles. It is necessary to examine the logic of the main provisions of the organization’s internal control due consideration of the requirements of international practice controls and propose principles of internal control. For this purpose, conducted a critical analysis of the main provisions of internal controls contained in the publications and in the regulations on internal control proceedings. Synthesis of articles of authors of lead scientific and practical journal Ukraine "Accounting and Auditing" for the 1994-2015 biennium pointed out that despite the coverage of current journal articles provisions, principles, requirements, rules and other modern techniques. On internal control and comprehensive set of reasonable response to the organization and classification of internal control is absent. This leads to continue the search key components of the organization’s internal control. The above basic concepts in publications on the organization of internal control were used in the formation of a set of principles of control. According to the requirements of the OECD field of internal control includes risk management, cost control, change in control, complete information to guarantee the effectiveness of internal control systems, providing the ability to make decisions and so on. COSO model contains an exhaustive list of five components. The results of the questionnaire trainees have provided compelling arguments for classifying and establishing relevant principles of organization and internal controls were rejected. A list of the basic principles of the organization of internal control, which consists of 25 elements that are shaped clarification obvious to professional economists, the contents of principles provides unambiguous interpretation. Proper organization of internal control can effectively use the limited resources of the enterprise, to achieve a significant effect.